Seni Khat : satu kajian Estetika Seni - Siti Hawa, bt. Ahmad. (Universiti Malaysia Sarawak (UNIMAS), 2007)
The purpose ofthis research is to identify the aesthetic value ofIslamic calligraphy (khat script) in Malaysian contemporary visual art scene. This research will represent the appreciation of beauty and the style that contain in khat script. This research will be used in creation ofpersonal artwork. To complete this study, the research will answer a few basic questions about the meanings, the history of khat writing and formal character in khat script also the style used by the 'khatat ' (khat writer). This basic question will be extended to the approach and the style ofkhatat used in their artwork. Furthermore, this research will also identify the essence and the purity in the Islamic Art context. The finding results will be used in several pieces of personal artwork which using the khat writing in the artwork.